INFLUENCE OF SOIL CONSOLIDATION AND THERMAL EXPANSION EFFECTS ON HEIGHT AND GRAVITY VARIATIONS - Romagnoli C.; Zerbini S.; Lago L.; Richter B.; Simon D.; Domenichini F.; Elmi C.; Ghirotti M. (My University, 2003)
The daily GPS height series of the Medicina station were analyzed for the period July 1996-September 2001. The station is located in the middle Po Plain on fine-grained alluvial deposits. A seasonal oscillation in the order of 18 mm (peak-to-peak amplitude) is present in the data. This crustal deformation has been modeled by including variations in the atmospheric, oceanic and hydrologic mass. The vertical positions can also be affected significantly by soil consolidation. Geotechnical parameters derived by in situ tests and laboratory analyses of the clayey soil collected at Medicina allowed the estimate of the soil settlement relevant to the seasonal oscillation of the surficial water table. Thermal expansion of the geodetic monument has to be taken into account in the case of high-precision vertical positioning. In this work models both for the soil consolidation and the thermal expansion effects are provided. The continuous gravity observations collected at Medicina by means of a superconducting gravimeter also exhibit a marked seasonal oscillation, which has been interpreted as the sum of loading and Newtonian attraction effects, as well as of the contribution due to soil consolidation. Especially the study concerning the soil consolidation effect has allowed a better insight on the seasonal vertical movements occurring at the Medicina station by providing quantitative information on soil behavior due to change of effective pressures. The results can be applied to those stations characterized by similar fine-grained soils and surficial hydrogeology.